The Consequences of Prior Initiation of Breast Feeding on Blood Glucose Levels in Neonates Born In a Tertiary Care Hospital - Rizwan-U- Zama; Ayesha Siddiqa; A.N. Thobbi; Tehseen Sajid Mudhol; R Shruthi (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Hypoglycemia is the most common event of failure of metabolic adjustments in the newborn. Changes in maternal and fetal monitoring techniques, administration of glucose-containing solutions during labor, delivery and early feeding in neonates significantly alter blood glucose concentrations during the first week of postnatal life. Subjects and Methods: A total of 90 healthy (60 born by FTND, 30 born by LSCS) term, AGA infants were longitudinally evaluated at birth, at one hour after feeds (post feed), and after 6 hours of life. Plasma glucose was estimated from Heel Prick capillary samples by glucometer method. The influence of mode of delivery, the interval between feeds, sex, birth weight, on blood glucose was analyzed. Results: The way of delivery did not affect the plasma glucose concentration in neonates. There was a substantial increase in blood glucose concentration after the first feed irrespective of their birth weight. It was found that female babies had a higher blood glucose concentration than male babies during our study period. All babies maintained normal blood glucose with the continuation of breastfeeding. Conclusion: Plasma glucose levels are satisfactorily maintained in healthy term infants without resort to pre-lacteal feeds and mode of delivery did not influence plasma glucose. There is no need to check blood glucose levels routinely in an asymptomatic, healthy, term, breastfed infants.